Predictive value of the preoperative prognostic nutritional index for postoperative progression in patients with pancreatic neuroendocrine neoplasms - Fu, Mengfei; Yu, Li; Yang, Liu; Chen, Yang; Chen, Xiao; Hu, Qinyu; Sun, Hui (Frontiers in Nutrition, 2022)
Objective: The preoperative nutritional status of cancer patients is closely related to prognosis. The prognostic nutritional index (PNI) has been shown to predict the prognosis of a variety of tumors, but its study in pancreatic neuroendocrine neoplasms (pNENs) is lacking. The aim of the present study is to investigate the predictive value of the preoperative PNI for postoperative progression in patients with pNENs. Methods: The medical records of 181 patients with pNENs, who underwent surgery, were retrospectively analyzed. A time-dependent receiver operating characteristic (ROC) curve was plotted to determine the optimal cut-off value of the preoperative PNI. Correlations between the preoperative PNI and clinicopathological parameters were analyzed using multiple linear regression. A Kaplan-Meier curve was applied to assess the progression-free survival (PFS) rate, which was tested using a log rank. Univariate and multivariate Cox proportional risk regression models were used to analyze the predictive value of the preoperative PNI on prognosis. Results: The optimal cut-off value of the preoperative PNI was 48.275. The patients were divided into a high PNI group (PNI > 48.275, n=92) and a low PNI group (PNI ≤ 48.275, n=89). The proportion of patients with tumor progression after surgery was significantly higher in the low PNI group compared with that in the high PNI group (P= 0.004). The Kaplan-Meier curve showed that the PFS rate after surgery was significantly lower in the low PNI group compared with that in the high PNI group (P=0.026). The preoperative PNI was an independent predictor of PFS (HR: 2.727, 95% CI: 1.174~6.333, P = 0.020). Conclusions: The preoperative PNI has a predictive value for postoperative progression in patients with pNENs.